Eye patching after cataract surgery is associated with an increased risk of short‐term corneal oedema. Issue 1 (22nd June 2020) - Gazit, Inbal; Dubinsky‐Pertzov, Biana; Or, Lior; Pras, Eran; Belkin, Avner; Einan‐Lifshitz, Adi
Abstract: Purpose: To evaluate the effect of postoperative eye patching after routine cataract surgery on corneal oedema and visual acuity on the first postoperative day. Setting: One public healthcare centre. Design and methods: This randomized controlled trial included patients undergoing uneventful cataract surgery in one medical centre. Patients were randomized into two groups: the surgical eye was patched with a single dose of a local steroid and antibiotic for 24 hr in the first group, and a plastic shield was used in the second with local steroid and antibiotic drops. The eyes were examined preoperatively and on the first postoperative day. Examination included the following: best‐corrected visual acuity (BCVA), full slit lamp examination, intraocular pressure (IOP), anterior chamber depth (ACD) and central corneal thickness (CCT) using the IOL Master 700 (Zeiss, Germany). Cumulative dissipated energy (CDE) and operation time were recorded for all cases. Results: One hundred eyes of 100 patients were included in the study. The postoperative increase in CCT 24 hr after surgery was 138 and 70 µm in the patched group as compared to the non‐patched group, respectively (p = 0.001). Best‐corrected visual acuity (BCVA) on the first postoperative day was 0.5 ± 0.45 LogMAR and 0.3 ± 0.3 LogMAR in the patched and non‐patched group, respectively (p = 0.01). There was no difference in CDE (11.33 ± 9.2 and 10.22 ± 7.3; p = 0.94) between the two groups. Conclusions: Eye patching after routine cataract surgery is associated with an increase in corneal oedema and slower visual recovery on the first postoperative day.